International intellectual property law (John Wiley, 1995)
This three-volume reference work provides an up-to-date analysis of the latest developments in the field. The first volume covers all of the major European countries, while the second examines the international property laws of major non-European countries. Both concentrate on intellectual property issues relating to trademarks, copyright, industrial design, patents, confidential information, and trade secrets. The third book surveys current global developments in intellectual property including forum shopping, unfair competition, Hag II, Mercosur, and the creation of trademark and patent law in diverse industry sectors